Phalloplasty in biological men with penile insufficiency. Issue 3 (June 2020) - Sinatti, Céline; Wolff, Dylan; Buncamper, Marlon; Verla, Wesley; Claes, Karel; Lumen, Nicolaas; Waterloos, Marjan; Monstrey, Stan; Hoebeke, Piet; Spinoit, Anne-Françoise
Summary: Introduction: Phalloplasty for penile insufficiency in biological men differs from trans-men by incorporating native tissue. The study objective was to report surgical and functional outcomes of phalloplasty in biological men. Patients & methods: Phalloplasty was performed with a radial free forearm (RFFA) or pedicled anterolateral thigh (ALT) flap. The tube-within-tube technique was used for urethroplasty. Complications <30 d postoperative were categorized according to Clavien-Dindo. Results: 30 patients, median (IQR) age of 21 (18–30)y, were included. 17 patients (57%) had penile insufficiency due to exstrophy or hypospadias surgeries, 7 patients (23%) due to sexual development disorders. In 16 patients RFFA was used. 19 patients needed urethroplasty, the rest catheterized through stoma. Median follow-up was 33 (14–80)mo. Within 30 d postoperative, 1 patients (3.3%) had Clavien-Dindo II and 6 patients (20%) Clavien-Dindo III complications. On long-term, 10 patients (33%) developed fistula, 6 needing urethroplasty. 7 patients (23%) had urethral strictures, all needing surgical intervention. All patients but one (98%) had erogenous sensitivity in the neo-phallus. All urethroplasty patients reported antegrade ejaculation. 16 patients (84%) voided through the urethra. 21 patients (70%) had an erectile device implanted. Conclusion: RFFA and ALT result in good erogenous sensitivity but fistulas and strictures are frequent.